2018
DOI: 10.1002/cne.24513
|View full text |Cite
|
Sign up to set email alerts
|

Marked interspecific differences in the neuroanatomy of the male olfactory system of honey bees (genus Apis)

Abstract: All honey bee species (genus Apis) display a striking mating behavior with the formation of male (drone) congregations, in which virgin queens mate with many drones. Bees' mating behavior relies on olfactory communication involving queen-but also drone pheromones. To explore the evolution of olfactory communication in Apis, we analyzed the neuroanatomical organization of the antennal lobe (primary olfactory center) in the drones of five species from the three main lineages (open-air nesting species: dwarf hone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 108 publications
(167 reference statements)
0
14
0
Order By: Relevance
“…MGs are therefore classic examples of how neuropil size reflects functional performance, as variation in their volume is generally associated with variation in sensitivity to their corresponding odour (Gronenberg and Hölldobler, 1999; El Jundi et al 2009b; Warner et al 2007; Miura et al 2009). Furthermore, MGC structure and composition is variable across closely related species, suggesting they may co-evolve adaptively with species specific ecological and behavioural traits (Kondoh et al 2003; Namiki et al 2014; Bastin et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…MGs are therefore classic examples of how neuropil size reflects functional performance, as variation in their volume is generally associated with variation in sensitivity to their corresponding odour (Gronenberg and Hölldobler, 1999; El Jundi et al 2009b; Warner et al 2007; Miura et al 2009). Furthermore, MGC structure and composition is variable across closely related species, suggesting they may co-evolve adaptively with species specific ecological and behavioural traits (Kondoh et al 2003; Namiki et al 2014; Bastin et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Tamura et al [38] reported that (E)-3-decenol and (Z)-3-decenol are separated by 6 and 25 KI units on an non-polar and polar column, respectively. The (Z)-3-decenol standard had a KI (semi polar: 1255, polar: 1788) and mass spectrum (55 (100), 67 (73), 68 (83), 81 (57), 82 (35), 95 (23), 96 (21)) that was similar to the large second chromatographic peak found in male samples (KI semi polar 1257 ±1; polar 1792 ± 1; mass spectrum: 55 (100), 67 (73), 68 (85), 81 (57), 82 (34), 95 (22), 96 (17)).…”
Section: Plos Onementioning
confidence: 99%
“…Different antennal response amplitudes were shown to be linked to glomeruli size, and are typically linked to specific olfactory receptors [72]. Sexually dimorphic enlarged glomeruli are typically linked to pheromone processing [73][74][75]. For example, the processing of the queen pheromone in the honeybee was linked to enlarged glomeruli in males [73].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…This structure is made of morphological and functional units called glomeruli, which individually gather inputs from a given type of OSN 28 30 . Recently, an increased effort has been made to describe and compare antennal lobe organization across species in Diptera 31 34 , Coleoptera 35 38 , Lepidoptera 39 44 and Hymenoptera 45 51 . The AL of social Hymenoptera stands out as particularly complex as it contains a high number of glomeruli, compartmentalized in clusters formed by distinct bundles of OSN axons 52 56 .…”
Section: Introductionmentioning
confidence: 99%